Cellulolytic bacteria associated with gut of yellow mealworm larvae (Tenebrio molitor, Coleoptera: Tenebrionidae) - isolation and molecular identification - Pastuszka, A.; Guz, L.; Ziętek, J.; Torbicz, M.; Szarek, K.; Oszust, M. (Polish Journal of Veterinary Sciences, 2026)
The study aimed to isolate and identify cellulolytic bacteria associated with the gut of yellow mealworm larvae (Tenebrio molitor) and to assess their main phenotypic and enzymatic features. Bacteria capable of utilizing cellulose as the sole carbon source were cultured on CMC medium under aerobic and anaerobic conditions. Molecular identification based on 16S rRNA gene sequencing revealed two isolates: Mammaliicoccus lentus (ML01) and Pseudocitrobacter vendiensis (PV02), both showing high sequence similarity to GenBank references (≥ 99.4%). Phylogenetic analysis confirmed their close relationship with corresponding species. Microscopy and biochemical tests indicated that ML01 is a Gram-positive, oxidase-positive coccus, whereas PV02 is a Gram-negative, oxidase-negative rod. Both strains exhibited γ-hemolysis and strong growth on TSA and LB media. API 20E profiling showed that ML01 could ferment several carbohydrates and produce β-galactosidase and arginine dihydrolase, while PV02 also expressed β-galactosidase activity. Cellulolytic activity, confirmed by Congo red and iodine staining, was observed in both isolates, with PV02 demonstrating the highest hydrolytic capacity. These findings indicate that the gut of T. molitor harbors cellulolytic bacteria with potential zoonotic risk, highlighting the need for their further monitoring.